Ultrarapid cerium(III)–NHC catalysts for high molar mass cyclic polylactide - Kerr, RWF; Ewing, PMDA; Raman, SK; Smith, AD; Williams, C; Arnold, PL (American Chemical Society, 2021)
Cyclic polyesters could improve the properties of degradable plastics, but routes to them that provide a product with faster rates, higher molar mass, and greater selectivity for cyclic vs linear polymer are needed. Here, homogeneous Ce(III)–N-heterocyclic carbene (NHC) catalysts show outstanding activities (turn-over-frequency (TOF) > 864 000 h–1), excellent control, and selectivity for cyclic polylactide (PLA) topology (>95%), yielding high molar mass PLA (60 < Mn < 250 kg mol–1). They efficiently produce cyclic PLA from rac-lactide or l-lactide and aliphatic cyclic polyesters from ε-caprolactone or β-butyrolactone. The enhanced performances are only achievable from combining cooperative Lewis acidic cerium(III) and hemilabile N-heterocyclic carbene functionalities.